The Image of Social Exclusion in Macedonian Media - Drakulovska Chukaleska, Marija; Dragovikj, Anica (University Goce Delchev, Shtip, 2019)
The paper explores the social exclusion within the media. The subject of the research is to identify the image of social exclusion within the Macedonian media. The main goal is to explore the social exclusion in terms of number, genre, source, and dimensions through which it is present in the selected media. In addition, it explores individuals and groups who are socially excluded, as well as entities that participate in their public articulation. The method of data collection is content analysis. In general, the results from the research show that media do not provide sufficient coverage of this topic, or in some cases, it is even misrepresented. Different media have different attitude towards the social exclusion. Selective approach and information with insufficient quality within the contents has been observed. The general conclusion is that the Macedonian media must urgently innovate ways and approaches for informing the public about social exclusion and at the same time, promote public debate on the problems of individuals and groups that are socially excluded. In this respect, we suggest a new, analytical and open approach to social exclusion in order to create appropriate public policies on this issue.
Keywords: social exclusion, media, public, individuals, groups, entities